Households’ acceptance of affordable Islamic public-private housing co-operative model (IPHCM) in Malaysia - Abdul Razak, D.; Bilal, M.; Hanudin bin Amin (Emerald Group Holdings Ltd., 2020)
Purpose: The purpose of this study is to examine the determinants influencing low- and middle-income households in accepting the Islamic public-private housing co-operative model (IPHCM) as an alternative to contemporary affordable public housing models in Malaysia. Design/methodology/approach: Using self-administrated questionnaires, data are collected from low- and middle-income households dwelling in Programme Perumahan Rakyat projects in Kuala Lumpur and the state of Selangor. The study used the theory of planned behaviour (TPB) and used the partial least squares technique to examine the proposed hypothesised relationships. Findings: The findings of this study suggest that subjective norm and perceived consumer religiosity is the most influential determinants affecting the behavioural intention of low- and middle-income households in accepting the IPHCM model. Attitude had a significantly positive relationship with households’ behavioural intentions towards accepting the IPHCM model. Practical implications: The findings of this study can serve as a guideline for policymakers to understand the behavioural intention of low- and middle-income households in accepting newly developed models in affordable public housing space. Originality/value: Behavioural aspects regarding the acceptance of affordable public housing models in Malaysia have yet to be profoundly explored in the literature. This study has extended the TPB by incorporating perceived consumer religiosity, in the affordable public housing domain, to analyse its effects on households’ acceptance of the IPHCM model. © 2020, Emerald Publishing Limited.